The Effect of Smoking on Corneal Biomechanics. (2nd January 2017) - Kilavuzoglu, Ayse Ebru; Celebi, Ali Riza Cenk; Altiparmak, Ugur Emrah; Cosar, Cemile Banu
ABSTRACT: Purpose : To determine the effect of smoking on corneal biomechanical behavior. Materials and Methods : The medical records of consecutive patients that presented to the ophthalmology department were reviewed. History of smoking and ophthalmological examination findings were recorded. The smoking group met the following criteria: a clear history of and present smoking habit, negative history of corneal disease and surgery, ocular response analyzer measurement at the time of examination, and a waveform score ≥3.7. Nonsmokers (never smoked or quit smoking ≥6 months earlier) that met the same criteria constituted the control group. Corneal biomechanical parameters were measured using ocular response analyzer. Data were analyzed using Pearson's χ 2 test, Mann–Whitney U test, and Spearman's correlation coefficient. Results : The smoking group included 166 eyes of 166 patients with a mean age of 38.7 ± 11.95 years, and the control group consisted of 170 eyes of 170 patients with a mean age of 38.40 ± 12.2 years. Mean cumulative smoking dose in the smoking group was 9.59 ± 11.87 pack-years (0.04– 75.00). There was no significant correlation between cumulative smoking dose and corneal hysteresis and corneal resistance factor ( P = 0.382 and 0.074, respectively). There were no significant differences in corneal hysteresis or the corneal resistance factor between the two groups ( P > 0.05). There was no significant difference in corneal hysteresis between those in the smoking group aged 18–44 years and those aged 45–64 years ( P = 0.258), whereas in the control group mean corneal hysteresis was significantly lower in the 45–64 year olds than in the 18–44 year olds ( P = 0.034). Conclusions : Although there was no significant difference in corneal biomechanics between smoking and control groups, the decrease in corneal hysteresis with aging was less apparent in the smoking group, which may be due to the potential changes in the cornea's microstructure induced by smoking during aging and the effect of smoking in aged corneal tissue viscosity.